Infrastructure and Core Quality Management Practices in Higher Education Performance - Ahmed Hani Mohammed; Che Azlan Bin Taib; Santhirasegaran Nadarajan (International Journal of Supply Chain Management, 2016)
The literature differs by choosing the quality management practices depending on the organization's activities or the type of sector. Meanwhile, there is a differentiation in selecting the best practices, even in the same sector. Malcolm Baldrige National Quality Award has resonated with researchers as the best practices that can conform to the higher education activities. Moreover, the literature discusses the impact of quality management practices on performance through being divided into Core and infrastructure practices. This study proposes to discuss any of these practices concerned with the Core-QMPs or Infrastructure-QMPs. It recommends being tested in the future.